2007
DOI: 10.1007/s10278-007-9075-y
|View full text |Cite
|
Sign up to set email alerts
|

Thick Slices from Tomosynthesis Data Sets: Phantom Study for the Evaluation of Different Algorithms

Abstract: Tomosynthesis is a 3-dimensional mammography technique that generates thin slices separated one to the other by typically 1 mm from source data sets. The relatively high image noise in these thin slices raises the value of 1-cm thick slices computed from the set of reconstructed slices for image interpretation. In an initial evaluation, we investigated the potential of different algorithms for generating thick slices from tomosynthesis source data (maximum intensity projection-MIP; average algorithm-AV, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
(18 reference statements)
0
28
0
Order By: Relevance
“…Chawla et al [62] based their study on mastectomy samples which they imaged with tomosynthesis and simulated lesions were added to the tomosynthesis volumes. At a dose level similar to single-view mammography, they found that the optimum number of projection images was 15 --17 at an angular range of 45 . The optimum angular spacing in both the studies conducted by Sechopoulos and Ghetti [50] and Chawla et al [62] was around 3…”
Section: Technical Aspects Of Bt Image Volume Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chawla et al [62] based their study on mastectomy samples which they imaged with tomosynthesis and simulated lesions were added to the tomosynthesis volumes. At a dose level similar to single-view mammography, they found that the optimum number of projection images was 15 --17 at an angular range of 45 . The optimum angular spacing in both the studies conducted by Sechopoulos and Ghetti [50] and Chawla et al [62] was around 3…”
Section: Technical Aspects Of Bt Image Volume Acquisitionmentioning
confidence: 99%
“…Detection of subtle details, like small tumors with low contrast, is therefore improved (Figure 2). For diagnostic purposes, a slice separation of 1 mm has commonly been used, but to reduce radiologist's reading time, which is directly connected to the number of slice images, projects are underway to generate thicker image slabs [45] and to study the effect of thicker slices on the detection of breast lesions.…”
Section: Breast Tomosynthesismentioning
confidence: 99%
“…Several reconstruction methods have been explored for use in DBT, including filtered backprojection (FBP) (Lauritsch and Haerer, 1998;Stevens et al, 2001;Claus et al, 2006;Mertelmeier et al, 2006), algebraic reconstruction (ART) (Kaczmarz, 1937;Andersen et al, 1984;Kak and Slaney, 2001;Kempston et al, 2006;Diekmann et al, 2007;Zhang et al, 2007) and maximum likelihood (ML) techniques (Wu et al, 2003;Wu et al, 2008). Unfortunately, the DBT reconstruction problem is under-defined, meaning that there exists an infinite set of possible solutions that satisfy the projection data, also known as the null space.…”
Section: Introductionmentioning
confidence: 98%
“…Detection of microcalcifications is essential since intraductal carcinoma (CIC) detected only through microcalcifications represent 19% of the cancers screened [30,31]. But 3D allows radiologists to use methods, such as the maximum intensity projection (MIP), specific to multislice imaging, to detect and analyze fine structures, such as microcalcifications [8,32]. This has not been assessed in our study.…”
Section: Discussionmentioning
confidence: 92%